DEVELOPMENT OF THE STRATEGIC QUALITY MANAGEMENT FOR CREATIVE TOURISM OF SUAN PHUENG MODEL - ชิณโชติ ปิรันธ์; จันทึก ธีระวัฒน์ (RMUTT Global Business and Economics Review, 2016)
This qualitative research included with 2 steps. First, in-depth interview with 17 stakeholders who related with tourism in Suan Phueng, Ratchaburi. Second, focus group with 12 stakeholders who related with tourism in Suan Phueng, Ratchaburi. The research found that the strategic quality management for creative tourism of Suan Phueng model will be the way to improve the tourism in Suan Phueng with collaboration of all stakeholders to promote tourism activities, products and services also conserving the nature and local culture at the same time. These will increase the number of quality tourist who will satisfy from learning and improve their skills by travelling in creative destination. The improvement of tourism in Suan Phueng will create economic prosperity to all stakeholders’ leads tourism sustainability to Suan Phueng. Then researcher proposed 9 factors of PESS+DIMPE which included, external factors 1) Performance 2) Efficiency 3) Standard 4) Satisfaction; and internal factors, 5) Destination 6) Innovation 7) Man 8) Process 9) Economic